Relasi Kuasa dan Ketimpangan Gender dalam Pembagian Harta Gono-Gini: Kajian Sosio-Legal Atas Putusan Perceraian Di Indonesia - Andi Nur Fikriana Aulia Raden; A.Ummu Fauziyyah Syafruddin (Jurnal Risalah Hukum, 2025)
The division of joint assets after divorce is a complex civil law issue because it not only involves legal norms, but is also influenced by social relations, gender, and power in the household. This study aims to examine how power relations and gender inequality shape the dynamics of the division of joint assets in divorce cases in Indonesia. Using a socio-legal approach, this study analyzes a number of court decisions and interviews with parties involved in the divorce process. The findings show that unequal access to legal information, patriarchal cultural pressures, and weak bargaining positions often disadvantage women in the process of dividing assets. In addition, factors such as legal awareness, the existence or absence of a prenuptial agreement, and trust in settlement mechanisms such as mediation or litigation also influence the form and outcome of property dispute resolution. Recommendations from this study include the importance of inclusive legal education regarding rights to joint assets and the development of more effective, fair, and gender-sensitive mediation methods to reduce conflict escalation in the divorce process. This research contributes to strengthening civil law policies that are responsive to the social conditions of Indonesian society.